An investigation of the expression of pigment genes in Mycobacterium avium subspecies paratuberculosis, strain K10 - Nguyen Le, Thanh (2017)
Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of paratuberculosis in ruminants and is a potential zoonotic pathogen associated with Crohn’s disease in humans. To date, two main types of MAP (Type S and Type C) have been identified which cause infections mostly in sheep or cattle, respectively. Pigment production is thought to be an exclusive characteristic of Type S strains of MAP; however work in this laboratory has shown that MAP C strains are able to induce carotenoid production following environment challenge. To initiate this study both Mycobacterium smegmatis and MAP K10 (a C strain) were grown on agar acidified to different pH levels and pigment production was induced in both species when the pH of the media was below 5.5. The cultures were grown aerobically to show that acid stress alone could induce the pigments. Comparative analysis of the genome sequence with carotenoid genes from other species of Mycobacterium revealed that there are highly conserved carotenoid biosynthesis genes in the MAP K10 genome. Comparison of the structure of this loci with other pigment operons in mycobacteria provided insights into the evolutionary history of carotenoid pigment and revealed that the genes present in MAP K10 are most closely related to those in M. avium and other subspecies of this group. Different RNA extraction methods were evaluated for gene expression analysis. Finally a modified TRIzol method was developed which met the criteria for the recovery of good quality mRNA for downstream applications. Comparison of the expression of the pigment genes under normal and acidic conditions revealed a general increase in expression for crt genes and also sigF, an alternative sigma factor that is known to regulate expression of genes in response to acid challenge in M. smegmatis. However not all of the crt genes were equally up-regulated suggesting that they are not co-transcribed in one operon.